ETNOGRAFIC REALIA AND TRANSLATION FEATURES - Guliruxsor Umarxonova (Journal of Higher Education and Academic Advancement, 2024)
The given article deals with study of ethnographic realia lexicon as well as interrelation of language and culture and analysis of which lies within translation, which is one of the most significant branches of modern linguistics. The aim of this research is to delve into the translation problems of ethnographic realia